Cover Feature: Proline Derived Bicyclic Derivatives through Metal Catalysed Cyclisations of Allenes: Synthesis of Longamide B, Stylisine D and their Derivatives (Eur. J. Org. Chem. 3/2020). Issue 3 (14th January 2020) - Jovanovic, Milos; Petkovic, Milos; Jovanovic, Predrag; Simic, Milena; Tasic, Gordana; Eric, Slavica; Savic, Vladimir
Abstract : The Cover Feature shows a synthesis of bromopyrrole alkaloids produced by marine sponges. While the silver‐catalysed route provides access to naturally occurring Longamide B and Stylisine D, the palladium route enables synthesis of analogues of these molecules. An intermediate involved in the key cyclisation step that bridges these methods is a proline derived allene. Details are discussed in the article by M. Jovanovic et al. We thank IRD / Philippe Borsa for kindly allowing us to use his original photo of the sponge Stylissa massa, a natural producer of Stylisine D. More information can be found in the Full Paper by M. Petkovic, V. Savic et al.